(3GdLGeY dYde GdbQBfs - (3Ydj Hf YjSi Hf Ydj GdQeGfj , J (B384 (3g`s
(3ChdgG (B:s
(3jbGd EPG cGfJ GdJhHI ef GdOfjG dG jUHM GdG HYOI bde bjd ef HYO Pdc s
(3BNQgG (B:s
(3hMSHfG Gddg hfYe Gdhcjd hfYe Gdhdi hfYe GdfUjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3eUOQ GbJfGA GdCUd (B:s
(3WTbfO (B(3137) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs